Impact Analysis of Generalized Audit Software (GAS) Utilization to Auditor Performances - Aries Wicaksono; Lusianah Lusianah (Bina Nusantara University, 2016)
This study aimed to understand whether the use of Generalized Audit Software (GAS) in the audit process had an impact on the auditors performance and to acquire conclusions in the evaluation form towards GAS audit process to provide a positive impact on the performance of auditors. The models used to evaluate the impact of GAS were Quantity of Work, Quality of Work, Job Knowledge, Creativeness, Cooperation, Dependability, Initiative, and Personal Qualities. The method used in this research was a qualitative method of analytical descriptive and evaluative, by analyzing the impact of the GAS implementation to the components of the user’s performance. The results indicate that the use of GAS has a positive impact on user’s performance components.